Changjiang and Kuroshio contributions to oxygen depletion on the Zhejiang Coast - Wu, Haokun; Yang, Wen; Zhang, Wenxia; Zhao, Xin (Frontiers in Marine Science, 2023)
In recent decades, intensified anthropogenic activities have resulted in increasing occurrence of hypoxia in the East China Sea. Kuroshio, as a natural factor, also threatens the oxygen content over the continental shelf. There have been many studies investigating the different contributions of Changjiang and Kuroshio to oxygen depletion over the continental shelf. This study revisited this issue and further investigated the mechanisms controlling the different role of Changjiang and Kuroshio in oxygen depletion and focused mainly on the Zhejiang Coast. A coupled high-resolution physical-biogeochemical model was used to investigate the connections between the variations in nutrients, chlorophyll, stratification, and oxygen and the delivery of Changjiang diluted water and Kuroshio subsurface water over the shelf, especially on the Zhejiang Coast in the summer of 2017. The distinct features of hypoxia off the Changjiang estuary (severe but transient) and that along the Zhejiang Coast (mild but prolonged) are caused by the different dynamic environments and nutrients sources. North of 30˚N, intense oxygen depletion and bottom hypoxia are typically under the constraint of Changjiang diluted water. While the impacts of upwelled materials associated with the Kuroshio subsurface water enhance southward with the simultaneously weakened impacts from the Changjiang diluted water. Besides confirming the support of upwelling on surface phytoplankton bloom along the Zhejiang Coast, this study detected subsurface chlorophyll maximum immediately underneath the main pycnocline offshore of the Zhejiang Coast during upwelling. This indicated that the upwelled oceanic nutrients were transported further offshore along isopycnals and also fertilized phytoplankton growth at the subsurface. The exacerbation of either anthropogenic or natural factors could potentially intensify oxygen depletion along the Zhejiang Coast.